2012
DOI: 10.1155/2012/417346
|View full text |Cite
|
Sign up to set email alerts
|

Ixora parvifloraProtects against UVB-Induced Photoaging by Inhibiting the Expression of MMPs, MAP Kinases, and COX-2 and by Promoting Type I Procollagen Synthesis

Abstract: Ixora parviflora with high polyphenol content exhibited antioxidant activity and reducing UVB-induced intracellular reactive oxygen species production. In this study, results of the photoaging screening experiments revealed that IPE at 1000 μg/mL reduced the activity of bacterial collagenase by 92.7 ± 4.2% and reduced the activity of elastase by 32.6 ± 1.4%. Therefore, we investigated the mechanisms by which IPE exerts its anti-photoaging activity. IPE at 1 μg/mL led to an increase in type I procollagen expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 52 publications
0
38
0
1
Order By: Relevance
“…The great number of plant extracts can diminish UVB-induced photo damage by decreasing activity of enzymes involved in tissue degradation (i.e., Ixora parviflora, Coffea arabica ) [39, 45], or by increasing of synthesis tissue constituents (i.e., Labisia pumila ) [43]. …”
Section: Discussionmentioning
confidence: 99%
“…The great number of plant extracts can diminish UVB-induced photo damage by decreasing activity of enzymes involved in tissue degradation (i.e., Ixora parviflora, Coffea arabica ) [39, 45], or by increasing of synthesis tissue constituents (i.e., Labisia pumila ) [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Repeated skin exposure to UVB can cause collagen breakdown resulting in an aged skin appearance such as wrinkle formation. The mechanism underlying UVB-induced collagen degradation is the generation of various reactive oxygen species (ROS) provoking the mitogenactivated protein (MAP) kinase pathway, which subsequently induces the expression and activation of matrix metalloproteinases (MMPs) in human skin fibroblasts (Moon et al 2008;Chiang et al 2012;Wen et al, 2012). These enzymes include collagenase-1 (MMP-1) and collagenase-3 (MMP-13), which are the primary mediators of connective tissue damage in skin following UV irradiation exposure (Ravanti et al 1999;Brennan et al 2003;Ahn et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have, therefore, focused on the development of MMP inhibitors as a promising antiphotoaging strategy [2]. In our previous study, we demonstrated that irradiation of human skin fibroblasts with UVB caused a decrease in cell viability and type I procollagen content and an increase in ROS production and expression of MMPs [7, 8]. In this study, we found that Neonauclea reticulata extract not only enhanced the proliferation of fibroblasts in a concentration-dependent manner but also exhibited a protective effect against UVB-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet B (UVB) irradiation stimulates the generation of reactive oxygen species (ROS) and induces the overexpression of MMP-1, -3, and -9 in human fibroblasts, resulting in the destruction of collagen and, hence, wrinkle formation and sagging skin [58]. Increased levels of ROS are known to alter the structure and function of genes and proteins in skin and MMPs, which are involved in extracellular matrix (ECM) remodelling, play important roles in cell migration, skin ulceration, and photoaging [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation